UPPER MIDLINE INCISION IN RECIPIENTS OF DECEASED-DONORS LIVER TRANSPLANTATION - Olival Cirilo Lucena da FONSECA-NETO; Américo Gusmão AMORIM; Priscylla RABELO; Heloise Caroline de Souza LIMA; Paulo Sérgio Vieira de MELO; Cláudio Moura LACERDA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2018)
ABSTRACT Background: Liver transplant (LT) is the only effective and long-lasting option for patients with end-stage liver disease. Innovations and refinements in surgical techniques occurred with the advent of transplants with partial grafts and laparoscopy. Despite these modifications, the abdominal incision remains with only few changes. Aim: Demonstrate the experience with the upper midline incision in LT recipients with whole liver grafts from deceased donors. Methods: Retrospective study with patients submitted to LT. Data were collected from the recipients who performed the surgical procedure through the upper midline incision. Results: The upper midline incision was used in 20 LT, 19 of which were performed in adult recipients. The main cause was liver disease secondary to alcohol. Male, BMI>25 kg/m² and MELD greater than 20 were prevalent in the study. Biliary complications occurred in two patients. Hemoperitoneum was an indication for reoperation at one of the receptors. Complication of the surgical wound occurred in two patients, who presented superficial surgical site infection and evisceration (omental). Two re-transplant occurred in the first postoperative week due to severe graft dysfunction and hepatic artery thrombosis, which were performed with the same incision, without the need to increase surgical access. There were two deaths due to severe graft dysfunction after re-transplant in 72 h and respiratory sepsis with multiple organ dysfunction in the third week. Conclusion: The upper midline incision can be safely used in LT recipients with whole grafts from deceased donors. However, receptor characteristics and hepatic graft size should be considered in the option of abdominal surgical access.